Geometric Parameters Influence on the Screw Withdrawal Strength of Coir Agglomerates - Ayrton Alef Castanheira Pereira; José Roberto Moraes D’Almeida (Journal of Natural Fibers, 2020)
This study aims to evaluate the screw withdrawal behavior of agglomerated panels fabricated with coir fibers and a polyurethane resin as binder. Based on design of experiments, an analysis was conducted to understand and describe the withdrawal behavior by evaluating the main parameters that affect panel/screw interaction. Using Box–Behnken method, the maximum withdrawal strength was predicted by a second-degree response model with good approximation. The model presented the optimum combination of the main parameters that govern panel/screw interaction, namely: screw nominal diameter, pilot hole diameter and screw depth of penetration. The latter showed the greatest contribution to withdrawal strength.